Migration of copper(II) ions in humic systems-effect of incorporated calcium(II), magnesium(II), and iron(III) ions - Klučáková, Martina; Enev, Vojtěch (Environmental science and pollution research international, 2024)
The mobility of heavy metals in natural soil systems can be affected by the properties and compositions of those systems: the content and quality of organic matter as well as the character of inorganic constituents. In this work, the diffusion of copper(II) ions in humic hydrogels with incorporated calcium(II), magnesium(II), and iron(III) ions was investigated. The methods of instantaneous planar source and of constant source were used. Experimental data yielded the time development of the concentration in hydrogels and the values of effective diffusion coefficients. The coefficients include both the influence of the hydrogel structure and the interaction of diffusing particles with the hydrogel. Our results showed that the presence of natural metal ions such as calcium, magnesium, or iron can strongly affect the diffusivity of copper in humic systems. They indicate that the mobility of copper ions depends on their concentration. The mobility can be supported by higher contents of copper in the system. While the incorporation of Ca and Mg resulted in the decrease in the diffusivity of copper ions, the incorporation of Fe(III) into humic hydrogel resulted in an increase in the diffusivity of Cu(II) in the hydrogel in comparison with pure humic hydrogel.
Keywords: Calcium; vápník; hořčík; Iron; Humic acid; huminové látky; Humic Substances; Ions; měď; Hydrogel; železo; Immobilization; Soil; Copper; půda; Diffusion; Magnesium; ionty